Development and Skin Penetration Pathway Evaluation Using Confocal Laser Scanning Microscopy of Microemulsions for Dermal Delivery Enhancement of Finasteride - Thirapit Subongkot; Natthan Charernsriwilaiwat; Rattathammanoon Chanasongkram; Kantawat Rittem; Tanasait Ngawhirunpat; Praneet Opanasopit (MDPI AG, 2022)
This study aimed to develop microemulsions using poloxamer 124 as a surfactant to improve the skin penetration of finasteride and to investigate the skin penetration pathways of these microemulsions by colocalization techniques using confocal laser scanning microscopy (CLSM). The prepared finasteride-loaded microemulsions had average particle sizes ranging from 80.09 to 136.97 nm with particle size distributions within acceptable ranges and exhibited negative surface charges. The obtained microemulsions could significantly increase the skin penetration of finasteride compared to a finasteride solution. According to the skin penetration pathway evaluation conducted with CLSM, the microemulsions were hair follicle-targeted formulations due to penetration via the transfollicular pathway as a major skin penetration pathway. Additionally, this study found that the microemulsions also penetrated via the intercluster pathway more than via the intercellular pathway and transcellular pathway. The intercluster pathway, intercellular pathway, and transcellular pathway were considered only minor pathways.